Impact of Remittance on Socio-Economic Development in Nepal (Patan Prospective Journal, 2025)
This paper based on examines the social and economic effects of remittances on rural livelihoods in Birendranagar Municipality–15, Surkhet, Nepal. It aims to analyze remittance flow patterns and assess their contribution to household-level socio-economic development. Using a mixed-methods approach, primary data were collected from 46 remittance receiving households through structured questionnaires and field observations, and analyzed using squantitative and descriptive techniques. The findings indicate that migrant workers are predominantly male with lower educational attainment, and Malaysia is the principal destination country. Remittances are mainly utilized for daily consumption, education, housing, and health services, resulting in improvements in living standards and access to basic facilities. However, remittance inflows tend to decline during periods of crisis, increasing household vulnerability. Given that remittances account for approximately 20–30 percent of Nepal’s GDP, their role in sustaining rural livelihoods is substantial. Although the findings are context-specific and not generalizable, the study highlights the significant influence of remittances on the socio-economic conditions of migrant households in Nepal.